MyPainting.nu. - Lokaal 01, Breda (Breda : Lokaal 01, 2009)
Timmermans, Ante ; Frize, Bernard ; Frings, Bert ; Palermo, Blinky ; Hardt, Bruno ; Van Eecke, Christophe ; Hollerer, Clemens ; Eecken, Dirk Vander ; Marcaccio, Fabian ; Houben, Hedwig ; Dorner, Helmut ; van der Loo, Huub ; Andriesse, Jan ; Voskuil, Jan Maarten ; McNab, Janice ; Vanderheyden, JCJ ; Bytebier, Jean-Marie ; De Wilde, Johan ; van der Sommen, Jos ; Wouters, Karel ; Goudzwaard, Kees ; Van Dessel, Kris ; Hendriks, Lieven ; Devriendt, Lucas ; Tuymans, Luc ; Schuppers, Martijn ; Otter, Olphaert den ; Vanden Eynde, Patrick ; Vermeersch, Pieter ; Hocks, Teun ; de Cordier, Thierry ; Raat, Thomas ; Tilman ; Gillen, Tina ; Sasnal, Wilhelm ; Malevich, Kasimir ; Zegers, Ben ; Fludd, Robert ; Bandau, Joachim ; Quix, Stefaan
Nederlands
Tentoonstelling "MyPainting.nu" in Lokaal 01, Breda, 19.04.2009 - 12.07.2009
boek